Familial mediterranean fever: A retrospective clinical and molecular study in the east of anatolia region of Turkey - Etem, Ebru Onalan; Deveci, Sukriye Derya; Erol, Deniz; Yuce, Huseyin; Elyas, Halit (My University, 2010)
Familial Mediterranean Fever (FMF) is an autoinflammatory periodic disorder. We aim to identify the distribution and the frequency of the Mediterranean Fever (MEFV) gene mutations in the east of Anatolia in Turkey and perform a genotype/phenotype correlation in the patients' cohort. The study was carried out on 415 clinically diagnosed Turkish FMF patients and 103 healthy controls. The tested individuals were screened for the most common twelve MEFV mutations. The most important features were the predominance of the M694V and E148Q mutations in patient group and the earlier of onset of the disease in M694V mutation carriers compared with the carriers of other mutations (P=0.00). We discuss the high frequency of E148Q mutations in patient group compared with controls, genetic counseling in intermarriage families and the variations in mutation frequency according to regions of Turkey. © Etem et al.; Licensee Bentham Open.
Keywords: Familial mediterranean fever; Genetic counseling; M694V mutation; Mutation screening